2016
DOI: 10.4238/gmr.15039009
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanism of maternal post-traumatic stress disorder in delayed rat offspring development: dysregulation of methylation and gene expression

Abstract: ABSTRACT. Maternal post-traumatic stress disorder (PTSD) increases the risk of adverse neurodevelopmental outcomes in the child. Epigenetic alternations may play an essential role in the negative effects of PTSD. This study was aimed to investigate the possible epigenetic alterations of maternal PTSD, which underpins the developmental and behavioral impact. 24 pregnant Sprague-Dawley (SD) rats were randomly grouped into PTSD and control groups. Open-field tests (OFTs), elevated pull maze (EPM) assays, gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…(Ishihama et al, 2010). Furthermore, mice whose dams were exposed to a posttraumatic stress disorder model (restrained for 2-h period and then forced to swim for a 20-min period with 6 other rats) had downregulated ADCYAP1 gene expression (Zhang et al, 2016). These studies support the potential influence of prenatal stress on the ADCYAP1 gene in this study and suggest altered behavioral effects due to prenatal stress.…”
Section: Gene Body Regions Differential Methylation Of 4363supporting
confidence: 79%
“…(Ishihama et al, 2010). Furthermore, mice whose dams were exposed to a posttraumatic stress disorder model (restrained for 2-h period and then forced to swim for a 20-min period with 6 other rats) had downregulated ADCYAP1 gene expression (Zhang et al, 2016). These studies support the potential influence of prenatal stress on the ADCYAP1 gene in this study and suggest altered behavioral effects due to prenatal stress.…”
Section: Gene Body Regions Differential Methylation Of 4363supporting
confidence: 79%
“…Therefore, PTSD symptoms are re-experienced due to dysfunction or imbalance of DA within the anxiety circuit areas of the medial prefrontal cortex, hippocampus, striatum, and amygdala [ 38 ]. Neurobiologic events leading to dysregulation of the DA system after SPS are supported by some studies of severe stressors, such as life events [ 1 39 ]. Disruption of anxiety-related circuitry or alterations in the stress-reactivating system following SPS in the medial prefrontal cortex, hippocampus, striatum, and amygdala may be related to dysfunction in other brain regions in patients with PTSD [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also show reduced tissue 5-HT levels in the mPFC, STR, AMYG, and HPC of SPS rats, suggesting a reduction in serotonergic tone in the mesolimbic pathway. Therefore, PTSD symptoms are reexperienced due to dysfunction in or imbalance of 5-HT within the anxiety circuit areas of the mRFC, STR, AMYG, and HPC [ 7 51 52 ]. We have shown that animals with PTSD treated with TMP had significantly increased 5-HT levels in the mRFC and HPC, and this may have inhibited the pathophysiology of PTSD.…”
Section: Discussionmentioning
confidence: 99%